Vestibular Disorder Approach Base on International Classification of Vestibular Disorder - Orlando Pikatan; I Ketut Sumada; Ni Ketut Candra Wiratmi; Desie Yuliani (AKSONA, 2022)
Vestibular symptoms are symptoms that interfere with daily activities. Diagnosing these symptoms often relies on radiologic examinations that lead to a false negative. Proper clinical approach and study showed higher accuracy than radiologic examination on vestibular disease. These clinical approaches are based on time, triggers, and targeted analysis. The new vestibular symptoms will be classified into acute vestibular syndrome, episodic vestibular syndrome, and chronic vestibular syndrome. An acute vestibular syndrome is a vestibular symptom that lasts for days up to weeks. The episodic vestibular syndrome is vestibular symptoms that periodically appear. The chronic vestibular syndrome is a vestibular symptom that appears from months to years. Diagnosing vestibular symptoms must be precisely made. The proper termination is the best way to facilitate doctors in communicating with each other. Using this classification is a precise and easy way to detect vestibular etiology.  This review is made for clinicians to determine and differentiate the etiology of the vestibular syndrome and gives information in uniforming nomenclature of vestibular symptoms.